Níveis de vitamina D em indivíduos brasileiros com glomerulopatias - Augusto, Frederico Knupp [UNIFESP] (2017)
INTRODUCTION: Patients with glomerulopathies have different levels of proteinuria and among the proteins lost there is the vitamin D binding protein. However, little is known about the levels of 25-hydroxyvitamin D [25(OH)D] and its relation to proteinuria in this population. OBJECTIVES: To evaluate possible associations between blood levels of 25(OH)D and those of 24-hour proteinuria, as well as between 25(OH)D levels and demographic, clinical and laboratory parameters, main medications and renal function decline. PATIENTS AND METHODS: in the present prospective cohort study, we evaluated 175 adult or elderly patients diagnosed with glomerulopathy, levels of 25(OH)D, calcium, phosphorus, PTH, urinalysis, serum creatinine, estimated glomerular filtration rate (eGFR), clinical and laboratory parameters, in collections performed between the months of August to October. RESULTS: In our sample, the mean age was 44.5 years ± 14.9, 62.9% were female and 50% white. The mean Body Mass Index (BMI) was 28 ± 5.1 kg/m2, proteinuria was 1.48 ± 2.18 g/24h, the eGFR was 75.9 ± 32.9 mL/min., and the follow-up of 1102 ± 494 days. We identified a high frequency of 25(OH)D deficiency and deficiency and an inverse relationship between its levels and those of proteinuria, regardless of the stage of chronic kidney disease (p < 0.001). Most patients were overweight or obese. BMI was significantly associated with reduced levels of 25(OH)D (p = 0.024). Among patients with more than 1 year of follow-up, levels of 25(OH)D < 15 ng/mL were associated with a higher rate of decline in eGFR (p = 0.017). CONCLUSIONS: There is an inverse association between vitamin D and proteinuria levels, regardless of the eGFR. Reduced levels of 25(OH)D were associated with high BMI, but not with age, gender and ethnicity or GFR. Levels of 25(OH)D < 15 ng/mL were associated with a faster decline in renal function. These findings suggest that vitamin D deficiency or insufficiency may have consequences on the progression of glomerulopathies and their progression to more advanced stages of chronic kidney disease.